The shaking of Al-Rusafi's vision of science and education from the perspective of religion and heritage (Journal of the College of Basic Education, 2023)
Al-Rusafi worked during his time and after it. It was a school in which manygood and bad principles and opinions, and a set of contradictory and good positions, withThis is a flag of Iraqi poetry in the modern era. aspects of his poetry and lifeFor decades, it has been the subject of many university studies and theses, and many books have been written about his poetry.A lot of research, but despite this, his book remains a source of endless studies for a good reason.It is that literary studies cannot be limited and codified, or that they end here or there.Everyone looks at the subject he is researching from a specific point of view that can be accepted or rejected.What distinguishes literary studies from purely scientific studies in which creativity may be exhausted at pubertyto a certain degree in some of its subjects.Among the topics of Al-Rusafi's poetry that the researchers concerned with was the subject of (scienceand education), and this vocabulary had a special importance for the poet and was one of the main themes.the task on which he wrote his poetry. As we study it here, we study it through the angles thatIt has been researched by many researchers, i.e. within the framework of the reformist poetry of the poet, but rather fromthrough a new point of view. This view stems from the analysis of this type of poetry byThe poet through his vision of religion and heritage, or in other words, the impact of religion and heritage on the vision ofAl Rusafi for Science and Education.Hence, we had to extract the poet's poetry through his huge collection of books.And related to the issue of science and education and the statement of the impact of Al-Rusafi's vision of this call throughAttraction or discord with the subjects of religion and heritage. From here, the research has occupied a number